TUJUAN, FUNGSI, SASARAN DAN MANFAAT SUPERVISI AKADEMIK - Fatkhan Munif (Pusat Studi Pendidikan dan Kreativitas Guru, 2018)
Supervision is a service from superiors to subordinates by givingdirection to improve performance for the be